Katekese Menuju KBG Yang Mandiri Dan Misioner - Elisabeth Merchi Habu; Intansakti Pius X (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Catechesis towards Independent and Missionary Faith Formation (KBG) is an approach in religious education aimed at nurturing individuals who are firm in their faith, capable of independently experiencing and practicing their religious beliefs, and ready to actively disseminate religious teachings to others. This approach combines catechesis, faith formation, and mission skills development. Through this process, individuals are expected not only to become passive recipients of religious teachings but also to become active agents of change in spreading religious values and strengthening their faith communities.